The talking eggs : a folktale from the American South - San Souci, Robert D.; Pinkney, Jerry (New York : Dial Books for Young Readers, 1989)
A Southern folktale in which kind Blanche, following the instructions of an old witch, gains riches, while her greedy sister makes fun of the old woman and is duly rewarded.
Caldecott Medal/Honor
Elem. School Library Collection
Wilson's Children
Booklist starred, March 1999
Elem. School Library Collection, June 2000
Notable/Best Books (A.L.A.), March 2009
Keywords: Folklore -- United States; Folklore -- United States